Factors associated with levels of anxiety in postpartum women hospitalized in an obstetrics service - Pinto, Cátia Sofia Pereira; Almeida, Carlos Manuel Torres; Castro, João Francisco de (O Mundo da Saúde, 2023)
Postpartum Anxiety is a frequent phenomenon, since the puerperium is the period of greatest risk for the onset or worsening of anxiety. It is usually manifested by irritability, fatigue, concentration difficulties, tension and sleep disturbances. It can have consequences both for the woman and for her relationship with the baby and her partner, interfering with the quality of life and the future of the family. Objective: to identify the factors that relate to the anxiety levels of postpartum women during hospitalization in an obstetrics service. Methodology: this is a descriptive, correlational and analytical quantitative study, with the application of the Zung Self-Rating Anxiety Scale, the Supportive Hospital Environment Design Scale and the Maternal Self-Perceived Scale of Neonatal Care Skills. Participants were 85 postpartum women who were hospitalized in the obstetrics service, in a hospital in the northern region of Portugal. Results: Most mothers (51.8%) had no anxiety, 11.8% had non-pathological anxiety and 36.5% had pathological anxiety. Of the anxiety factors studied, a global relationship was established between the level of postpartum anxiety and the perception of neonatal care skills (p=0.00). Conclusion: The postpartum women showed greater anxiety in the Central Nervous System (CNS) dimension. A better perception of social support in the hospital environment reduces levels of maternal anxiety in different aspects. The higher the maternal self-perception of skills in caring for the baby, the lower the level of postpartum anxiety.